2015
DOI: 10.1161/circresaha.116.304269
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Reversion of Cardiac Myocyte Fate During Mammalian Cardiac Regeneration

Abstract: Rationale Neonatal mice have the capacity to regenerate their hearts in response to injury, but this potential is lost after the first week of life. The transcriptional changes that underpin mammalian cardiac regeneration have not been fully characterized at the molecular level. Objective The objectives of our study were to determine if myocytes revert the transcriptional phenotype to a less differentiated state during regeneration and to systematically interrogate the transcriptional data to identify and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
136
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(156 citation statements)
references
References 41 publications
15
136
0
1
Order By: Relevance
“…6H). During regeneration, dedifferentiating zebrafish and mouse cardiomyocytes disassemble the sarcomere for cell division to proceed (Jopling et al, 2010;Porrello et al, 2011), and high levels of sarcomeric proteins are characteristic of differentiated cardiomyocytes (O'Meara et al, 2015). Confirming the RNA-seq data, we detected fewer woundadjacent cardiomyocytes showing decreased levels of myosin light chain kinase 3 (mylk3), which regulates sarcomere assembly (Seguchi et al, 2007), in hearts after RO treatment than in DMSO-treated hearts (Fig.…”
Section: Notch Signalling Regulates Cardiomyocyte Proliferation and Dsupporting
confidence: 74%
“…6H). During regeneration, dedifferentiating zebrafish and mouse cardiomyocytes disassemble the sarcomere for cell division to proceed (Jopling et al, 2010;Porrello et al, 2011), and high levels of sarcomeric proteins are characteristic of differentiated cardiomyocytes (O'Meara et al, 2015). Confirming the RNA-seq data, we detected fewer woundadjacent cardiomyocytes showing decreased levels of myosin light chain kinase 3 (mylk3), which regulates sarcomere assembly (Seguchi et al, 2007), in hearts after RO treatment than in DMSO-treated hearts (Fig.…”
Section: Notch Signalling Regulates Cardiomyocyte Proliferation and Dsupporting
confidence: 74%
“…Elegant studies by Porrello and colleagues have shown that neonatal mouse hearts still possess the ability to regenerate by reactivation of cell division in cardiomyocytes and that this ability gets lost within the first week after birth [39]. Recent studies have correlated a regenerative capacity with a specific transcriptional signature, which resembles a more immature phenotype [40]. It was postulated that the trigger for the switch may be the oxygen-rich environment after birth and a residual population of smaller cardiomyocytes with hypoxic characteristics and increased proliferative potential was identified [41].…”
Section: Establishment Of Cytoarchitecture During Developmentmentioning
confidence: 99%
“…In the current issue of Circulation Research, O'Meara et al 6 analyzed the transcriptional signature of mouse hearts at different stages of postnatal development (p0, p4, p7, and 8-to 10-week-old mice) and of embryonic stem cells undergoing cardiac differentiation. RNA-sequencing analysis revealed increased expression of multiple genes, which function in mitochondrial, sarcoplasm, and sarcomere-specific processes whereas genes primarily involved in RNA processing (RNA transport, RNA splicing, and RNA capping) and cell cycle were downregulated.…”
Section: Article See P 804mentioning
confidence: 99%